Eksplorasi Visual Diri dalam Desain Karakter - Homan, Devi Kurniawati (Humaniora, 2014)
In a visual communication, the main thing is a communication which can solve the existing problems, not just as something beautiful to look at and considered. The most important part in designing visual communication when the communication is correct, attractive and persuasive. Semiotic understanding becomes important to study in the early stages of designing a visual communication that is intended to improve the effectiveness of communication. Semiotic itself is the study of the meaning of a sign in a particular context. To more easily understand the meaning of the sign, then the practice of visual meaning in the form of character design is made. This study was conducted to make students understanding of the meaning of a sign in a particular context through self-exploration. With the relation between the object being studied by each individual then a design experience will arise. This experience will create a more meaningful and in-depth exploration to students in the understanding of their studies about the meaning of a sign in a particular context. This study is used the method of visual exploration strategy that is commonly used by designers to convey the idea.